The Effectiveness of EthnoSTEM-Based Science Learning to Improve Junior High School Students' Science Literacy Ability - Bramastia Bramastia; Suciati Suciati; Febriani Sarwendah Asri Nugraheni; Meida Wulan Sari; Icha Kurnia Wati; Bayu Antrakusuma; Dyah Fitriana Masithoh (Postgraduate, University of Mataram, 2023)
The low scientific literacy of students needs to be improved through the teaching materials used in learning. Teaching materials can be combined with various learning models including Ethno-STEM. The research aims to develop and test the feasibility of a module on vibrations and waves material in empowering science literacy ability of class VII students. The type of research carried out is development research using the 4D method including the define, design and develop stages. In this article, the research stage is written only up to the development stage. In the define stage, an analysis of gaps occurring in the field is carried out to define what is needed in the development process. In the design stage, the researcher prepares a product design according to the needs that have been summarized in the define stage. In the development stage, researchers began to develop modules according to needs and then carried out feasibility tests. Validation was carried out on aspects of material, media, language and learning. The overall module validation results obtained were 0.91 with valid criteria. Therefore, it can be concluded that the vibrations and waves module is effective to improve students' science literacy ability